(3QSGdI aj NhGU CSeGA Gddg JYGdis - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; NhGU CSeGA Gddg JYGdi hgh GdYdj aj WdH GdEjeGf jG Gddg jG QMje cPdc aj WdH GdEjeGf jG Gddg jG Ydje aj WdH GdYUeIs
(3BNQgG (B:s
(3hgj CQHYI CSeGA eLedI GdCSeGA eCJj GSe hKeGfjI hKeGfhf CSeGA eJOGNdI HYVgG aj HYV aGage Pdcs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3QSGdI GfTGFjI dfYeI Gddg Gdhdj (B- (3QSGdI QhMGfjIs
Keywords: (3GdJhMjO hGdedd hGdfMds